Parenting Patterns with Development of Social Adaptation for Toddler Age Children - Haniarti Haniarti; Ariana Juhartina; Usman Usman (LPPM IAIN Parepare, 2021)
Parenting patterns are a description of the attitudes and behavior of parents and children in interacting and communicating during parenting activities. The purpose of this study was to determine the relationship between democratic, authoritarian, permissive parenting with the development of adaptation for toddlers at the Posyandu in the working area of ​​the Bojo Baru Health Center, Barru Regency. This research is an analytic survey research with an observational study with a cross-sectional study design. The data analyzed using the chi-square test (x2) with a significant level of = 0.05. There are 67 respondents who met the research criteria. The chi-square test (x²) showed that there was a relationship between democratic parenting (p = 0.02), authoritarian (p = 0.01), permissive (p = 0.03) with the development of adaptation of toddler age children at the Posyandu in the working area of ​​the Bojo Baru Health Center, Barru Regency. Based on the results of the study, we concluded that there was a relationship between democratic, authoritarian, permissive parenting with the development of social adaptation of toddler age children at the Posyandu in the working area of ​​the Bojo Baru Health Center, Barru Regency.